A randomized controlled trial comparing the techniques and suture material used for skin closure in supra public transverse incision at caesarean surgery. - Jayawardane, D.B.I.A (My University, 2007)
To compare subcuticular 2/0 polyglycolic acid continuous closure with 2/0 nylon interrupted mattress closure of Joel Cohen skin incision for lower segment caesarean section with regard to cosmetic appearance, of the scar, surgical site complications and surgical time. Women were randomly allocated to two groups. In the subcuticular group the skin incision was closed by 2/0 polyglycolic acid subcuticular Suture and in the nylon group by 2/0 nylon interrupted mattress sutures 3 cm apart after following a standardized method for the LSCS. Subsequent surgical site complications were documented up to hospital discharge and 8 weeks post delivery. Cosmetic appearance of the scar at 8 weeks.